Morphology of ovule, seed and pollen grain of Rafflesia R. Br. (Rafflesiaceae) - Sofiyanti, Nery; Yen, Choong Chee (Bangladesh Journal of Plant Taxonomy, 2012)
The ovules, seeds and pollen grains of 24 Rafflesia specimens from nine species were examined. The ovules and seeds of all specimens showed similar shapes and structures. Rafflesia ovules are J-shaped and incompletely anatropous, while the seeds are chestnut-shaped. The pollen grains are small (10-25 ?m in diameter), prolate-spheroidal and subprolate, monoporate, with a smooth surface and no ornamentation. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13124 Bangladesh J. Plant Taxon. 19(2): 109-117, 2012 (December)